2012
DOI: 10.1016/j.joca.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of fibrotic and chondrogenic process in the capsule of idiopathic frozen shoulders

Abstract: In addition to fibrosis and inflammation, which used to be considered the main pathology of frozen shoulders, chondrogenesis is likely to have a critical role in pathogenesis of idiopathic frozen shoulders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 47 publications
4
51
0
Order By: Relevance
“…In our recent report relating the capsule of idiopathic frozen shoulders (contracture of the shoulder joints), expression of chondrogenic factors as well as inflammatory and fibrotic factors significantly increased (Hagiwara et al 2012). Other factors, such as abnormal cross-linking of collagens and expression of chondrogenic factors, may affect the degradation mechanism (Lee et al 2010;Hagiwara et al 2012).…”
Section: Discussionmentioning
confidence: 93%
“…In our recent report relating the capsule of idiopathic frozen shoulders (contracture of the shoulder joints), expression of chondrogenic factors as well as inflammatory and fibrotic factors significantly increased (Hagiwara et al 2012). Other factors, such as abnormal cross-linking of collagens and expression of chondrogenic factors, may affect the degradation mechanism (Lee et al 2010;Hagiwara et al 2012).…”
Section: Discussionmentioning
confidence: 93%
“…It was difficult to know the precise mechanism of worse prognosis in diabetes mellitus, but excessive glucose concentration might lead to a faster rate of collagen glycosylation and cross-linking of collagens, which might restrict the shoulder motion [21]. Further, a recent study indicated that chondrogenic changes of the capsule were observed in patients with recalcitrant idiopathic frozen shoulder [22]. Therefore, the association between recalcitrant idiopathic frozen shoulder and cross-linking and the chondrogenic process of the capsule must be examined in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with DNase I (Invitrogen, Carlsbad, CA, USA), RNA was amplified using the Amino Allyl MessageAmp II aRNA Amplification kit (Ambion, Austin, TX, USA) and labeled with Cy3 and Cy5, then hybridized to a whole Human Genome Microarray 4 × 44 K (Agilent Technologies, Santa Clara, CA, USA) at 65°C for 17 h (Yamayoshi et al 2012). The array was scanned with GenePix 4000B (Molecular Devices, Downingtown, PA, USA), and the scanned image was analyzed with GenePix Pro 6 software (Molecular Devices) (Hagiwara et al 2012). To obtain gene expression profiles, probes for which the average expression level was upregulated (> 3.0 times) or downregulated (< 1/3 times) in satellite cells from the SSP muscle were compared with those from the SSC muscle (Hagiwara et al 2012;Yabe et al 2015).…”
Section: Dna Microarraymentioning
confidence: 99%
“…The array was scanned with GenePix 4000B (Molecular Devices, Downingtown, PA, USA), and the scanned image was analyzed with GenePix Pro 6 software (Molecular Devices) (Hagiwara et al 2012). To obtain gene expression profiles, probes for which the average expression level was upregulated (> 3.0 times) or downregulated (< 1/3 times) in satellite cells from the SSP muscle were compared with those from the SSC muscle (Hagiwara et al 2012;Yabe et al 2015).…”
Section: Dna Microarraymentioning
confidence: 99%